Crystal structure of Campylobacter jejuni peroxide regulator. Issue 13 (14th June 2018) - Sarvan, Sabina; Charih, François; Butcher, James; Brunzelle, Joseph S.; Stintzi, Alain; Couture, Jean‐François
Abstract : In Campylobacter jejuni (Cj), the metal‐cofactored peroxide response regulator (PerR) transcription factor allows C. jejuni to respond to oxidative stresses. The crystal structure of the metalated form of Cj PerR shows that the protein folds as an asymmetric dimer displaying structural differences in the orientation of its DNA‐binding domain. Comparative analysis shows that such asymmetry is a conserved feature among crystallized PerR proteins, and mutational analysis reveals that residues found in the first α‐helix of Cj PerR contribute to DNA binding. These studies present the structure of Cj PerR protein and highlight structural heterogeneity in the orientation of the metalated PerR DNA‐binding domain which may underlie the ability of PerR to recognize DNA, control gene expression, and contribute to bacterial pathogenesis. Abstract :